MENGKAJI NILAI-NILAI KEARIFAN LOKAL PERANG OBOR TERHADAP SEMANGAT NASIONALISME - Noor Fitrian, Alvin; Septiyani, Wulan (PPKn, Fakultas Keguruan dan Ilmu Pengetahuan Universitas Palangka Raya, 2021)
Humans and culture are two inseparable elements. Culture is a natural wealth that is created because of hereditary customs created by humans themselves. The Torch War in Tegalsambi Village, Jepara Regency is one example of a culture that has been inherent for a long time. The Torch War is a traditional performance attraction as an expression of gratitude to God Almighty. The Torch War has local wisdom values ??such as togetherness, mutual cooperation, tolerance, empathy, solidarity, and religion. The greatness of the soul in a pluralistic nation is very important for the continuity of life in society, nation and state. The values ??of local wisdom from a culture must be able to strengthen its identity as a nation that has a spirit of nationalism. This research examines the values ??of local wisdom contained in the torch war tradition in terms of the spirit of nationalism which refers to Pancasila as the basis for the philosophy of the Indonesian nation. The method used in assessing the values ??of local wisdom of the Torch War against the spirit of nationalism is descriptive qualitative analysis. The analysis was carried out based on an in-depth literature study by prioritizing data and facts from the field. The results of the description in this study indicate that the values ??of local wisdom contained in the torch war tradition are in line with the norms of life which are based on the points of Pancasila as the basis of the nation's philosophy.